A Revisited Renewable Consumption-Growth Nexus: A Continuous Wavelet Approach through Disaggregated Data - Bilgili, Faik; Kuskaya, Sevda; Toguc, Nurhan; Mugaloglu, Erhan; Kocak, Emrah; Bulut, Umit; Baglitas, H. Hilal (Pergamon-Elsevier Science Ltd, 2019)
In this research, we aim at exploring the influence of renewables on industrial production (Ip) in the US by following continuous wavelet coherence and partial continuous wavelet coherence analyses. To this end, we observed the co-movements between, biofuels and Ip, solar and Ip, wind and Ip, geothermal and Ip, wood and Ip, and, waste and Ip in the US for the monthly period from January 1989 to November 2016. The primary motivations behind this research are twofold. Firstly, it attempts to reach the co-movements, if exists, between renewables' consumption and industrial production by following time domain and frequency domain analyses. Secondly, it aims at observing the potential co-movements between renewable energy sources (geothermal, solar, wind, biofuels, wood, and, waste) and Ip by adding some control variables (fossil fuels, total biomass etc.) into the wavelet models to understand clearly the responses of the industrial production to the impulses in renewables in both short term and long term periods. The paper hence eventually reveals significant effects of geothermal, wind, solar, biofuels, wood, and, waste on US industrial production in short term cycles and long term cycles. Thereby, following this paper's results of continuous wavelet analyses which depict the impact of renewables on US economy at 1-3-year frequency and 3-8-year frequency for the time period from January 1989 to November 2016, one might provide policy makers with relevant current and future efficient renewables' energy policy for the US and other countries which have similar structures with the US.
Toguc, Nurhan/0000-0002-3891-1163; Bulut, Umit/0000-0002-8964-0332; Mugaloglu, Erhan/0000-0001-5362-6259; Bilgili, Faik/0000-0003-4138-6897; Kocak, Emrah/0000-0002-5889-3126; Baglitas, Hayriye Hilal/0000-0002-3031-6271; Kuskaya, Sevda/0000-0003-4527-5713
Keywords: Wavelet Analyses; Continuous Wavelet Coherence; The US Economy; Geothermal; Wind; Solar; Biofuels; Wood; Waste